Pengaruh Reward Non Finansial Terhadap Kinerja Pegawai di Kantor Kecamatan Sukodono Kabupaten Sidoarjo - Miftachul R, Nanda; Supriliyani, Ni Wayan; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2020)
ABSTRACT As a government agency under the supervision ofthe Sidoarjo Regional Personnel Agency. Sukodono Sub-District Office successfully made an achievement in 2018 as the Clean Serving Bureaucracy Region which was obtained from the Ministry of Civil Service Administration and Bureaucratic Reform. This triggers researchers to find out how much influence an award has on employee performance. In this study, researchers used a quantitative method in which to collect data using questionnaires / questionnaires and interviews and linking two variables that have been determined. After the researchhas been carried out, it can be obtained that there is an effect of rewards on the performance of the facilitators. This means that an increase in awards will lead to an increase in the performance of employees of the Sukodono subdistrict office in Sidoarjo Regency. Keywords: Reward, Performace, Human Resource Management